2010
DOI: 10.2217/pgs.10.50
|View full text |Cite
|
Sign up to set email alerts
|

Association of HTR2C , But Not LEP or INSIG2 , Genes with Antipsychotic-Induced Weight Gain in a German Sample

Abstract: The results contribute to the accumulating evidence for an association of the X-chromosomal HTR2C gene with antipsychotic-induced BWG. The proposed underlying mechanisms include decreased HTR2C gene expression with reduced 5-HT-modulated activation of hypothalamic proopiomelanocortin-neurons, and inverse 5-HT(2C) agonism in the presence of D(2) receptor antagonism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 53 publications
5
52
1
4
Order By: Relevance
“…Most consistent findings exist for an association between polymorphisms of the HTR2C gene and AIWG. The functional polymorphism -759C/T 122 has repeatedly been shown to influence AIWG, with the C allele being overrepresented in patients with higher AIWG (for example, see Reynolds et al, 123 Miller et al, 124 and Opgen-Rhein et al, 125 including 2 metaanalyses, see De Luca et al 126 and Sicard et al 127 ). Although negative findings have been reported, 128,129 with one study indicating the opposite allele as a risk variant, 130 to date, the role of this polymorphism is supported by the most robust studies.…”
Section: Antipsychotic-induced Weight Gainmentioning
confidence: 99%
See 2 more Smart Citations
“…Most consistent findings exist for an association between polymorphisms of the HTR2C gene and AIWG. The functional polymorphism -759C/T 122 has repeatedly been shown to influence AIWG, with the C allele being overrepresented in patients with higher AIWG (for example, see Reynolds et al, 123 Miller et al, 124 and Opgen-Rhein et al, 125 including 2 metaanalyses, see De Luca et al 126 and Sicard et al 127 ). Although negative findings have been reported, 128,129 with one study indicating the opposite allele as a risk variant, 130 to date, the role of this polymorphism is supported by the most robust studies.…”
Section: Antipsychotic-induced Weight Gainmentioning
confidence: 99%
“…Although negative findings have been reported, 128,129 with one study indicating the opposite allele as a risk variant, 130 to date, the role of this polymorphism is supported by the most robust studies. Other HTR2C polymorphisms have been shown to be associated with AIWG as well, including the -995G/A, -1165A/G, 125 and Cys23Ser polymorphisms as part of a high risk haplotype. 127 Leptin plays a major role in energy homoeostasis.…”
Section: Antipsychotic-induced Weight Gainmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Several studies linking HTR2C (Cys23Ser and -759C.T) polymorphisms to weight gain have been conducted, with significant [57][58][59][60] and nonsignificant [136][137][138][139][140] results. A recent meta-analysis of 522 schizophrenia individuals suggested that the -759C allele is associated with weight gain.…”
Section: Studies Assessing the Adverse Effects Of Clozapinementioning
confidence: 99%
“…144 Other genes with significant associations include ADRA2A, 51,52 BDNF, 53 DRD2, 54,55 adiponectin, C1Q and collagen domain containing (ADIPOQ), 50 melanocortin 4 receptor (MC4R), 63 protein kinase beta 2 non-catalytic subunit (PRKAB2), 65 protein kinase gamma 2 non-catalytic subunit (PRKAG2), 50 and roundabout axon guidance receptor homolog 1 (ROBO1). 66 Controversial results were observed for HTR2A 57,136 (positive and negative results, respectively), insulin induced gene 2 (INSIG2) 60,61,145 (positive results only in the second study), leptin (LEP) 60,62 (negative and positive results, respectively), protein kinase alpha 2 catalytic subunit (PRKAA2) 50,65 (negative and positive results, respectively), and TNF 67,137,146 (positive results only in the second study). No correlation was observed for adrenoreceptor beta 3 (ADRB3), 144 cholecystokinin (CCK), 147 cannabinoid receptor 1 (CNR1), 148 fatty acid binding protein 3 (FABP3), 50 fat mass and obesity associated (FTO), 50 peroxisome proliferator-activated receptor gamma (PPARG), 149 protein kinase alpha 1 catalytic subunit (PRKAA1), 50 protein kinase gamma 1 non-catalytic subunit (PRKAG1), 50 protein kinase gamma 3 non-catalytic subunit (PRKAG3), 50 72,73 were associated with risk of metabolic syndrome induced by clozapine or risperidone/olanzapine.…”
Section: Studies Assessing the Adverse Effects Of Clozapinementioning
confidence: 99%